Accessing Heart Health: A Northern Experience - Katherine Timmermans; Ellen Rukholm; Isabelle Michel; Lisa Seto Nielsen; Jennifer Lapum; Robert P Nolan; Jan E Angus (Rural Nurse Organization; Binghamton University, 2011)
Background and Research Purpose: Coronary heart disease (CHD) continues to be a major cause of death and disability across the globe. Regional differences in CHD exist throughout Canada, including Ontario. It is important to explore the complex interplay between geographical regions and individuals' efforts at reducing their cardiovascular risk. This study explored barriers and supports to heart healthy lifestyles and associated meanings within various regions of Ontario. The focus of this paper is on the northern context to better understand the issues these individuals face when making heart healthy lifestyle changes. Sample and Method: The study used an ethnographic approach and photo-elicitation interviews. Participants took photographs of places that represented the barriers and supports to lifestyle changes for cardiovascular risk modification. These photographs were used as the basis for interview dialogue. Twelve informants from a larger study comprised the northern sub-sample considered in this paper. Results and Conclusions: When the data were analyzed, health care access and access concerns related to heart healthy lifestyles for people in northern Ontario emerged as key findings. Findings suggest that the concept of place is pivotal to recognizing issues related to health care access, which should be incorporated as part of our understanding of health and cardiovascular risk modification.